2021
DOI: 10.1136/bmj.n415
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality in Wuhan city and other parts of China during the three months of the covid-19 outbreak: findings from nationwide mortality registries

Abstract: Objective To assess excess all cause and cause specific mortality during the three months (1 January to 31 March 2020) of the coronavirus disease 2019 (covid-19) outbreak in Wuhan city and other parts of China. Design Nationwide mortality registries. Setting 605 urban districts and rural counties in China’s nationally representative Disease Surveillance Point (DSP) system. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
90
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 33 publications
5
90
2
4
Order By: Relevance
“…China was among the countries that had applied nationwide NPIs at the early epidemic. Since the fourth week of January, 2020, accompanying the block of Wuhan city [ 14 , 15 ], massive interventions including the isolation of the confirmed/suspected cases and quarantine of close contacts, even the strict and unprecedented measures like closure of school and entertainment venues, banning of mass gathering activities, have been implemented across China to contain the spread of COVID-19 [16] . At the individual level, the use of facemasks and hand washing at public areas had been encouraged widely in China.…”
Section: Introductionmentioning
confidence: 99%
“…China was among the countries that had applied nationwide NPIs at the early epidemic. Since the fourth week of January, 2020, accompanying the block of Wuhan city [ 14 , 15 ], massive interventions including the isolation of the confirmed/suspected cases and quarantine of close contacts, even the strict and unprecedented measures like closure of school and entertainment venues, banning of mass gathering activities, have been implemented across China to contain the spread of COVID-19 [16] . At the individual level, the use of facemasks and hand washing at public areas had been encouraged widely in China.…”
Section: Introductionmentioning
confidence: 99%
“…Wuhan where the pandemic is assumed to have originated, had a very high RMR and an eight-fold increase in pneumonia mortality in the first three months of the pandemic suggested that Covid-19 went largely underreported. Interestingly, mortality from non-communicable diseases also increased by 20% [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…An example of this is the lower morbidity and mortality from COVID-19 seen in China. Despite a high allele frequency of 0.50 of the at-risk IFITM3-rs-12252 allele among the Chinese population, the mortality and morbidity were low in China in the first 3 months of the outbreak excluding Wuhan (Liu et al, 2021 ). The lead author of the study attributes the low mortality in China to the lockdown and associate behavioral changes like facemasks, increased hygiene, social distancing and travel restrictions.…”
Section: Discussionmentioning
confidence: 99%